POLITICAL IDENTITY DILEMMA: ELECTORAL AFFILIATION OF NU TRENGGALEK CITIZENS WITH PKS IN SOCIOLOGICAL PERSPECTIVE - Cahyono, Agus; Teguh, Teguh; Khamami, Akhmad Rizqon (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study examines the phenomenon of electoral affiliation of some Nahdlatul Ulama (NU) members in Trenggalek towards the Prosperous Justice Party (PKS), which represents a new dynamic in the local political configuration and creates a political identity dilemma. Historically, NU members are known to have political and ideological closeness to the National Awakening Party (PKB). However, in recent years, there have been signs of a change in electoral preferences towards PKS, a party with a more modernist Islamic orientation. This study aims to understand the factors that drive this affiliation and analyze its impact on the collective identity of NU members and the local political map in Trenggalek. The method used is a literature study (library research) with a qualitative approach, where data is collected through literature studies of books, scientific journals, research reports, and other scientific sources relevant to the theme of Islamic politics, religion-based voter behavior, and religious identity. The results of the study indicate that this electoral shift is influenced by PKS's adaptive strategy in the approach to preaching and political communication that accommodates NU traditions, disappointment with PKB's performance at the local level, and the openness of the young generation of NU to alternative political choices. However, this convergence has created identity tensions, especially among NU figures who view PKS as a threat to traditional values. The implications of this study indicate the importance of an inclusive approach in Islamic politics and the need for a reorientation of Islamic parties in responding to the dynamics of local community religious identities and aspirations in a contextual and sensitive manner